The prevalence of adverse drug reactions ADR in patients at a tertiary care hospital in Nepal a pilot study - Anuj Mishra, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
The prevalence of adverse drug reactions ADR in patients at a tertiary care hospital in Nepal a pilot study